Textiles and clothing in the Uruguay Round: Current situation and future perspectives - Konrad Neundörfer (Intereconomics, 1990)
The success of the entire Uruguay Round of the GATT depends considerably upon the success of the negotiations on the liberalization of world trade in textiles and clothing, since a number of developing countries have made their support for progress in the negotiations on services or safeguards contingent upon progress in this field. What are the present controversies? And what are the chances of resolving them in time?
Keywords: 330; Multi-Fibre Arrangement